Antibiofilm activity of bromelain from pineapple against Staphylococcus aureus - Silva, Michelle Pereira; Calomino, Mariana Alcântara; Teixeira, Lenise Arneiro; Barros, Rosana Rocha; Paula, Geraldo Renato de; Teixeira, Felipe Lopes (Acta Scientiarum. Biological Sciences, 2023)
Bromelain is a set of proteolytic enzymes usually obtained from pineapple (Ananas comosus). Although bromelain has distinguished therapeutic properties, little is known about its proteolytic potential against opportunistic pathogens related to wound healing complications, such as Staphylococcus aureus. This study aimed to investigate the antibiofilm and antibacterial activity of bromelain in 43 clinical strains of S. aureus isolated from chronic wounds and blood cultures. Bromelain’s activity against S. aureus biofilm in vitro was assessed by analyzing biofilm formation in cultures grown in the presence of 1% bromelain and biofilm destruction after the addition of 1% bromelain to mature biofilms. Proteinase K and sodium metaperiodate were also added to mature biofilms in parallel to compare their activity with that of bromelain and, together with exopolysaccharide and protein production rate assays, to determine the chemical composition of the biofilm extracellular matrix of selected strains of S. aureus. Bromelain was also evaluated for its DNase activity and impact on cellular hydrophobicity and auto-aggregation. Mueller-Hinton agar dilution was used to determine bromelain minimal inhibitory concentration (MIC). Biofilm assays showed that 1% bromelain significantly inhibits S. aureus biofilm formation (p = 0.0157) by up to 4-fold and destroys its mature biofilms (p < 0.0001) by up to 6.4-fold, both compared to the control grown without bromelain. Biofilms of methicillin-resistant S. aureus strains isolated from chronic wounds were the most affected by bromelain treatment. No antibacterial activity was detected with bromelain MIC assays and the proteolytic activity of bromelain was identified as the main antibiofilm mechanism of the enzyme, though its DNase activity may also contribute. The epithelial therapeutic properties of bromelain combined with its antibiofilm activity against S. aureus make it a promising alternative to compose the therapeutic arsenal for the control of S. aureus biofilms in the context of wound care.